Towards a critical realist approach to the dark side of digital transformation - Wheaton, Jamie; Kreps, David (Frontiers in Human Dynamics, 2023)
The Dark Side of Information Systems (IS) is a school of thought which explores the detrimental consequences that can arise from IS phenomena such as digital transformation (DT). Critical Realism (CR), meanwhile, is a philosophical approach which can lend a deeper understanding of dark phenomena thanks to its emphasis upon the role of deep-lying, generative mechanisms. However, as our paper demonstrates, the extant research base applying a CR approach in the exploration of dark phenomena in general is small with respect to examining the potential dark consequences of DT. Our paper therefore introduces the CR philosophical approach to the research of dark phenomena, through a case study of the digital transformation of Britain’s land-based betting industry. This example highlights how a CR approach unearthed a generative mechanism formed by the productivity of digital platform-based forms of gambling. Whilst platforms provide novel gambling markets and ease-of-access which may be seen positively by the consumer, our example shows that the generative mechanism formed by the productivity of platform gambling gives rise to the continuous exploitation of staff and customers alike in addition to the continuous accumulation of capital by operator. We demonstrate that, as opposed to specific, pre-identified dark phenomena such as addiction or technostress, dark phenomena caused by generative mechanisms may be unknown, perceived positively or differently over time. A CR approach can facilitate a deeper understanding of how these generative mechanisms and subsequent dark phenomena emerge and evolve, and promote wiser approaches to DT.